Design and Development of Mach-zehnder Interferometer Fiber Sensor for Structural Health Monitoring - Png, Wen Hao (2019)
Structural health monitoring is important to our life as losses in resources and lives can occur if deflection and damage of civil structure and pipeline system can not be detected immediately. This thesis presents a novel study on structural health monitoring based on optical fiber sensor, which includes the curvature sensing and crack monitoring using the packaged fiber-based in-line tapers Mach-Zehnder Interferometer (MZI) curvature sensor, as well as the Loop integrated Mach-Zehnder Interferometer (LMZI) optical fiber sensor in pipeline monitoring and vibration sensing. A highly sensitive tapers MZI sensor with curvature sensitivity up to 1.65 mW/M-1 was fabricated and implemented in concrete monitoring. In the lab tests, three MZI sensors were embedded into the Lightweight Foamed Concrete Structural (LWFCS) beams with different polypropylene percentages (0.4 %, 0.25 % and 0 %) to characterize the sensor performance according to the concrete environments of different tensile capacities. MZI sensor managed to hold up to a maximum loading force of 26 kN in the concrete environment before it stopped functioning. The resultant optical powers of MZI sensors were mapped to the strains measured by the lead wire alloy foil strain gauges (brand: TML, model: FLK-6-11), and achieved a good correlation up to 0.968. Furthermore, double-sided sensing property of MZI sensor had advantage over the conventional strain gauge in detecting the internal cracking of concrete before any earlier sighting of the surface macrocracks. A low frequency vibrational LMZI sensor with torsional sensitivity up to 0.0216 mW/° was fabricated and implemented in the pipeline monitoring. The LMZI sensor was characterized according to the discrete changes of frequencies range from 20 Hz to 500 Hz and showed good accuracy and reliability in the frequency response. In both 3 m galvanized steel pipeline and 40 m large scale pipeline test, the LMZI sensor able to detect the vibrations induced by the water flow during normal flow conditions, as well as the additional leak-induced vibrations during the leak events. The frequency responses of the LMZI sensor were compared to the Accelerometer (model: Kistler 8704B50T) and show good agreement with percentage variations of 0.4% and 2.64% in the 2 bar and 3 bar, respectively.